Activation of Content-Schemata for Scaffolding L2 Writing: Voices from a Turkish Context - Kufi, Elmaziye Ozgur (Springer/Plenum Publishers, 2023)
It has been observed that Turkish university students suffer in L2 writing when they lack background knowledge about the writing topic. Triggered by this observation, this study intended to explore effectiveness of content-schemata activation for scaffolding Turkish students in their challenging L2 writing practices. Study participants, students studying at an English-medium university in Turkey, were asked to write an essay on a specific topic at the beginning of the week before participating in any activities and then they were asked to write a second essay on the same topic after being engaged in various skills activities designed to activate their content-schemata. The same procedure was repeated for seven weeks with a different topic each week. To gather data, students' first and second essays were compared and students' and teachers' perceptions regarding their experiences in English writing classes were elicited through questionnaires. As study findings reveal that content-schemata activation leads to the production of better essays in terms of content and that both students and teachers are positive about the use of skills activities for idea generation prior to essay writing, integration of activities that would activate students' content-schemata into the language curriculum in other ESL/EFL educational contexts is highly recommended.
Keywords: Writing skill; L2 writing; Insufficient world knowledge; Content-schemata activation; Integrated-skills approach to writing